Service climate and organization trust in Sara-Ed Trading Sdn Bhd / Mohammad Farid Mohamed Marzuki and Rose Mato - Mohamed Marzuki, Mohammad Farid; Mato, Rose (2014)
Research is about creation and development; this is essential to increase the understanding of service quality and service climate and the trust in the organization. Climate can be defined as employee's perception of kinds of behaviour that are rewarded and supported in a particular setting (Schneider, 1990). An organizational climate, for example describes the shared perception of all individuals in an organization aggregated to the organizational level.